Habitat structure, breeding stage and sex affect hunting success of breeding Red-backed Shrike (Lanius collurio). Issue 2 (2nd April 2016) - Morelli, F.; Mróz, E.; Pruscini, F.; Santolini, R.; Goławski, A.; Tryjanowski, P.
Abstract : Perch-sites are a necessary component for birds that employ a sit-and-wait foraging strategy, like Red-backed Shrikes ( Lanius collurio ). However, little is known about the influence of perch characteristics and its relation to the foraging substrate, elements that influence prey-capture success. This study was conducted in parallel in Italy and Poland and is based on > 5000 min of behavioural observations in the field. Our results show that perch type and foraging substrate characteristics affect the hunting behaviour of the Red-backed Shrike. The species utilises for its hunting activities mainly human-related structures. The foraging substrates most frequently used were ground (surface in cultivated, uncultivated, grassland and roads) and air; and secondarily the vegetation (mainly foliage of shrubs or trees). The average hunting success rate was 60%, but there were differences between Italy and Poland. Hunting success was highest for a combination of perch types (shrubs and foraging substrate on ground), and also from power lines in order to capture prey on roads. Although roads were less frequently used than other foraging substrates, they offered the highest hunting success. We found no effects of sex, period of day or weather conditions on hunting success. However, success rate increased during the last stages of the breeding season, i.e. during hatching and feeding of nestlings. The wide variety of preys and foraging substrates recorded in this study are typical for an opportunistic bird species. Open, warm spaces appear to constitute prime foraging habitat for the species, and some human-related structures as barbed wires, power lines and marginal hedges offer preferred support as perch-sites. Then, the presence and combination of some of these structures can help to improve the success rate of hunting attempts of Red-backed Shrikes. Our results can constitute a useful tool for ecological planning and enhance the conservation of this typical species of agricultural landscapes.